Age of the introduction of the first complementary food and determinants of its early introduction by Slovak mothers - Slávka Mrosková; Alena Schlosserová; Dagmar Magurová (University of Ostrava, 2016)
Aim: To assess the age of introduction of complementary food (CF) and the factors leading to early introduction of CF (≤ four months). Design: Cross-sectional study. Methods: In the period October 2011 to April 2012 we conducted research on 405 mothers of infants living in the Slovak Republic, particularly in the regions of Prešov (56.0%) and Košice (20.5%). The questionnaire, of our own design, integrated 13 factors. Statistical analysis included descriptive statistics and logistic regression (95% CI). Results: The first CF was introduced at 5.5 months (M = 5.47; SD = 1.22; range 1.0 to 10.0). Early introduction of CF was identified in 24.2% of children. A significantly higher risk of early introduction of first CF was found in respondents with: lower maternal age (OR = 4.436), lower levels of education (secondary education without GCE/vocational qualifications - OR = 10.140), lower maternal awareness of healthy nutrition (OR = 2.996), lower levels of satisfaction with their financial situation (OR = 1.927), and in single mothers (OR = 5.143), and children receiving combined milk nutrition rather than purely breastfeeding (OR = 3.888). Conclusion: Recognition of the factors leading to early introduction of CF allows the implementation of effective prevention strategies by health professionals.